Avaliação Institucional Interna na perspectiva da coordenação pedagógica - Fonseca, Sueli Holanda (2016)
This research work is based in a qualitative study approach and has as general aim: to understand the relation of the Internal Institutional Evaluation with the work of two Pedagogical Coordinators (PC), that are also responsible for the applying of the tool with the teachers from the scholar unity, in a State Elementary II and High School of São Paulo State, under the supervision of the South 3º Regional Board of Education (BE). The questioning proposed were: How an Internal Institutional Evaluation may contribute to improve the teaching quality in a school when it is well applied, especially by the PC of the school? Which elements, from this evaluation tool, may support a better action of the PC in the school and in his or her relationship established with different actors – the principal, the teachers and the scholar community? As theoretical background, we choose to work with Brandalise (2007), Fernandes (2002), Dias Sobrinho (1996, 2003), Almeida (2005), Sousa (2000) and Souza (2010). These authors of the institutional evaluation help us to understand the theoretical reflection overview about the elaboration and implementation of an evaluation process and its decision-making process. The work is organized in three chapters, being the third and last chapter, which has the data analysis, divided in three axis: the duties of the Pedagogical Coordinator and his or her view about the school daily work: scholar routine and planning; the action of the PC on the management of the internal institutional evaluation: application of the tool and the use of its results in the school unity; and the actions of the PC in the teacher’s continuous training process, and in the relationship with the school leaders and scholar community. The results of this research leave some clues to us about the way one may improve the pedagogical management of the institutional evaluation process, the teachers training, and, also, about the relationship with the scholar community, in order to contribute to a better teaching quality in the school unity